The New Management Environment in Globe Silk Store - Nair, Sivadas Govindan (1999)
Globe Silk Store is renown locally owned departmental store, which is owned by the Tirathrai family. They have a total of fou r outlets spread across the Klang valley, Kuantan and Malacca. Globe Silk Store has been i n retail since 1930 and that makes them one of the pioneers in retailing. It was founded by Mr. Tirathdas Jethanand and since then it has gone though three generation with Vijay Kishu taking over from his father, Tan Sri Kishu, in 1993. Globe Silk Store has grown from its h u mble beginning, in Segamat, to one of a truly Malaysian shopping centre. With the change i n leadership i n 1993, came a series of changes i n its operations, which was i ntroduced by Vijay himself. This case study examines these changes and identifies the i mplications of these changes and the solution to be i mp lemented in Globe Silk Store. The case study is divided into two parts, where part A covers the case write up, while part B covers the case analysis. The elements covered in part A are company history, leadership styles and achievements, the restructuring, customer , retail stores, cash flows, the management team, and the next step.While part B covers the analysis, where the issue and problems are identified. T he case has a total of three problems, with the main issue of how staff could not cope up with the rapid changes. To solve the problems, a total of seven alternative solutions are recommended, which covers from short-term implementation to long-term implementation. One of the i mplementation solutions was the use of a change model. Finally, the part B ends with possible implementation strategies, which coves for both short-term and longterm.